La pandemia e le donne del mondo accademico - Strickland, Elisabetta (B@belonline, 2020)
The lockdown due to Covid-19 in Italy started on March 8th, the International Women’s Day. All Italians were asked to remain at home and do remote-working whenever possible. Universities and schools have been closed, lessons and seminars had to go on via various digital platforms. But the idea of thousands of people dying in hospitals because of the coronavirus kept the people in a permanent state of grief. Moreover women in academy, after being more or less liberated from domestic chores, all of a sudden found themselves back to the traditional role of women, i.e. taking care of their house and family. Which meant that their lives went back of at least fifty years. Again it seemed obvious that the problem of gender equity can no longer be postponed.